Survey on Odorous Mineral Gases in the Air Around the Wastewater Treatment Plant: A Case Study in a Stabilization Pond - Ali Arezoumand; Hamzeh Ali Jamali; Hamid Karyab; Reza Ghanbari; Saeed Omidi (Hamadan University of Medical Sciences, 2017)
Malodors are one of the problems of water and wastewater treatment plants, especially in the vicinity of residential areas. Mineral compounds like hydrogen sulfide (H2S) and ammonia (NH3) produce unpleasant smells in the wastewater treatment plants. These gases also have adverse effects on both humans and the environment. After field visits around the plant, a number of 12 sampling stations were determined. Sampling stations were selected from 4 cardinal directions with regard to permanent trade winds and on distances of 0, 2 and 4 km from the plant. Sampling was performed in the morning and evening during the four seasons. Jacob and Indophenol methods were used for measuring the concentration of H2S and NH3. According to analysis of variance (ANOVA) and Tukey test, and concentrations of NH3 and H2S during different seasons, the emissions were more significant in the warm seasons and caused more malodors (P = 0.011, P = 0.004 for NH3 and H2S, respectively). Moreover, there was a significant relationship between the concentration of NH3 and sampling sites (P = 0.000). However, the relationship between the concentration of H2S and sampling stations was not significant (P = 0.179).According to the results, the concentrations of H2S and NH3 in all the seasons except for winter were within the threshold limits. The concentration of H2S in the summer and the concentration of NH3 in all the seasons were higher than USEPA standards and World Health Organization (WHO) guidelines.